2020
DOI: 10.1186/s12889-020-09884-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community-based intervention for health and economic empowerment of marginalized women in India

Abstract: Background Empowered women have improved decision-making capacity and can demand equal access to health services. Community-based interventions based on building women’s groups for awareness generation on maternal and child health (MCH) are the best and cost-effective approaches in improving their access to health services. The present study evaluated a community-based intervention aimed at improving marginalized women’s awareness and utilization of MCH services, and access to livelihood and savings using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…Evidence shows that engagement of the community brings about equitable and high-quality MNCH services [ 26 ]. Empowering women on health and economic aspects has shown to have positive impact on improving awareness and utilizing maternal, neonatal and child health related services as well as uplifting livelihood of the community people [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that engagement of the community brings about equitable and high-quality MNCH services [ 26 ]. Empowering women on health and economic aspects has shown to have positive impact on improving awareness and utilizing maternal, neonatal and child health related services as well as uplifting livelihood of the community people [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In eight studies the country’s government 6 47–53 was responsible for initiating WGs. Information was unavailable for two documents 54 55. Twenty-two studies reported WGs that were new or remobilised2 6 23–25 27–34 36 39 40 44 45 50 52 54 55 and the remainder used existing groups 35 38 41 46 48 49 51 53.…”
Section: Resultsmentioning
confidence: 99%
“…Information was unavailable for two documents 54 55. Twenty-two studies reported WGs that were new or remobilised2 6 23–25 27–34 36 39 40 44 45 50 52 54 55 and the remainder used existing groups 35 38 41 46 48 49 51 53. All groups included MCH education, two-way learning, awareness raising or information sharing components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations